42.0k views
1 vote
What does c equal in thus equation I don't know for the life of me help is deeply appreciated 4(3+c)+c=c+4

User Praveen
by
5.6k points

1 Answer

4 votes

Answer:

-2

Explanation:

Step 1: Simplify both sides of the equation.

4(3+c)+c=c+4

(4)(3)+(4)(c)+c=c+4(Distribute)

12+4c+c=c+4

(4c+c)+(12)=c+4(Combine Like Terms)

5c+12=c+4

5c+12=c+4

Step 2: Subtract c from both sides.

5c+12−c=c+4−c

4c+12=4

Step 3: Subtract 12 from both sides.

4c+12−12=4−12

4c=−8

Step 4: Divide both sides by 4.

4c

4

=

−8

4

c=−2

User Akshansh Thakur
by
6.0k points